Adsorption and Corrosion Inhibition Effect of N-(l-Morpholinobenzyl)urea onMild Steel in Acidic Medium - M. Anwar Sathiq; A. Jamal Abdul Nasser; P. Mohamed Sirajudeen (E-Journal of Chemistry)
The influence of N-(l-morpholinobenzyl)urea (MBU) on corrosion inhibition of mild steel in 1 M HCl was studied by weight loss, effect of temperature, potentiodynamic polarization and electrochemical impedance spectroscopy. The experimental results showed that the inhibition efficiency increases with increasing of MBU concentrations but decreases with increasing temperatures. The adsorption of MBU on the mild steel surface obeyed the Temkin’s adsorption isotherm. Potentiodynamic polarization curves showed that MBU acted as a cathodic inhibitor predominantly in hydrochloric acid. This was supported by the impedance measurements which showed a change in the charge transfer resistance and double layer capacitance indicating adsorption of MBU on the mild steel surface. Protective film formation against the acid attack is confirmed by SEM.